PENGARUH LABA BERSIH DAN ARUS KAS OPERASI TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Kharisma, Putri; L. Tobing, Vargo Christian (EDUTECH CONSULTANT, 2020)
Dividend policy is a decision of a company to distribute profits generated in the form of dividends or will be retained in the form of retained earnings. Dividend policy is influenced by net income and operating cash flow. The purpose of this study is to determine whether there is an influence between net income and operating cash flow on dividend policy. The independent variables in this study are net income and operating cash flow, while the dependent variable in this study is the dividend policy measured by the dividend payout ratio. The population in this study were manufacturing companies on the Indonesia Stock Exchange in 2014-2018. The sample in this study were 45 data consisting of 9 companies and 5 years of research. The method used in this research is descriptive statistics, classic assumptions, and influence tests. The results of this study the researchers found that partially net income had no significant effect on dividend policy measured using the dividend payout ratio and partially operating cash flow did not significantly influence the dividend policy measured using the dividend payout ratio. Partially, net profit and operating cash flow together do not significantly influence dividend policy as measured by dividend payout ratio.